A Study on the Effect of Valeric Acid in Alzheimer's Induced Rats by the Estimation of Aβ 1-42 Biomarker - Dulla, Blessina Sugandhi; S., Bindhu; K., Leena Pramod (Journal of Health and Allied Sciences NU, 2021)
The effect of valeric acid on the behavior of Alzheimer's disease (AD)-induced rats by aluminum chloride (100 mg/kg body weight) was assessed using elevated plus maze (EPM) and the Hebb Williams maze (HWM). Amyloid β 1–42(Aβ1–42) biomarker was estimated by ELISA. In this study, valeric acid-treated rats were compared with those treated with piracetam (200 mg/kg), rivastigmine (0.5 mg/kg), and the results showed the rats treated with valeric acid had a very less transfer latency of EPM and HWM when compared with other standard drugs. In addition, valeric acid-treated rats showed reduced levels of amyloid β1–42 biomarker in the plasma. Hence, this study found that valeric acid may be suggested as a better drug for Alzheimer's disease.
Keywords: Alzheimer's disease; amyloid β 1–42; elevated plus maze; Hebb Williams maze; valeric acid